2011
DOI: 10.1016/j.ydbio.2011.05.667
|View full text |Cite
|
Sign up to set email alerts
|

Muscles in a mouse model of spinal muscular atrophy show profound defects in neuromuscular development even in the absence of failure in neuromuscular transmission or loss of motor neurons

Abstract: A mouse model of the devastating human disease "spinal muscular atrophy" (SMA) was used to investigate the severe muscle weakness and spasticity that precedes the death of these animals near the end of the 2nd postnatal week. Counts of motor units to the soleus muscle as well as of axons in the soleus muscle nerve showed no loss of motor neurons. Similarly, neither immunostaining of neuromuscular junctions nor the measurement of the tension generated by nerve stimulation gave evidence of any significant impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

20
110
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(133 citation statements)
references
References 69 publications
(133 reference statements)
20
110
2
Order By: Relevance
“…Importantly, no consensus has been reached regarding the cellular and molecular pathways whose perturbation results in SMA pathology. Identifying the cellular pathways most sensitive to decreased SMN is essential to understand how SMN depletion causes neuronal dysfunction/death in SMA and to accelerate therapy development.One of the early events in SMA pathogenesis is the loss of neuromuscular junction (NMJ) function, evidenced by muscle denervation, neurofilament accumulation, and delayed neuromuscular maturation (25)(26)(27). In addition, reduced neurotransmitter release and decreased numbers of docked vesicles that precede axonal degeneration and/or motor neuron death have been reported at synapses of severe SMA mouse models (28,29).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, no consensus has been reached regarding the cellular and molecular pathways whose perturbation results in SMA pathology. Identifying the cellular pathways most sensitive to decreased SMN is essential to understand how SMN depletion causes neuronal dysfunction/death in SMA and to accelerate therapy development.One of the early events in SMA pathogenesis is the loss of neuromuscular junction (NMJ) function, evidenced by muscle denervation, neurofilament accumulation, and delayed neuromuscular maturation (25)(26)(27). In addition, reduced neurotransmitter release and decreased numbers of docked vesicles that precede axonal degeneration and/or motor neuron death have been reported at synapses of severe SMA mouse models (28,29).…”
mentioning
confidence: 99%
“…One of the early events in SMA pathogenesis is the loss of neuromuscular junction (NMJ) function, evidenced by muscle denervation, neurofilament accumulation, and delayed neuromuscular maturation (25)(26)(27). In addition, reduced neurotransmitter release and decreased numbers of docked vesicles that precede axonal degeneration and/or motor neuron death have been reported at synapses of severe SMA mouse models (28,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, how suboptimal levels of SMN lead to SMA is largely unknown. Multiple studies in SMA mouse models revealed widespread synaptic defects in neuromuscular junctions (NMJs), including neurofilament accumulation, poor terminal arborization, immature endplates, reduced quantal content, disturbed calcium homeostasis, and decreased remodeling potential; these defects precede motor neuron death (Cifuentes-Diaz et al 2002;Le et al 2005;Jablonka et al 2007;Kariya et al 2008;Murray et al 2008Murray et al , 2012Kong et al 2009;Ling et al 2010;Ruiz et al 2010;Lee et al 2011), suggesting that the NMJ alterations are the initial consequence of SMN deficiency, Ó 2015 Hua et al This article is distributed exclusively by Cold Spring Harbor Laboratory Press for the first six months after the full-issue publication date (see http://genesdev.cshlp.org/site/misc/terms.xhtml). After six months, it is available under a Creative Commons License (Attribution-NonCommercial 4.0 International), as described at http:// creativecommons.org/licenses/by-nc/4.0/.…”
mentioning
confidence: 99%
“…Muscle atrophy is one of the two hallmarks of SMA. However, although there is a reduction in muscle fiber number and size (due to compromised muscle growth, lack of myofiber maturation, and premature differentiation of satellite cells), the importance of muscle SMN levels in SMA pathology is controversial (Braun et al 1995;Gavrilina et al 2008;Lee et al 2011;Hayhurst et al 2012). Martinez et al (2012) recently demonstrated that increased SMN in muscle-including myoblasts and satellite cells, two cell types critical for muscle growth and maintenanceslightly extends the survival of SMA mice, supporting the conclusion that the deficiency of SMN in muscles also contributes to the mortality of SMA mice.…”
mentioning
confidence: 99%